Negative electrode material and secondary battery
By introducing the kernel and shell structure in the negative electrode material of the lithium ion battery, using the transition metal carbide and carbon matrix filling agent to solve the problem of the volume expansion and circulation performance of the lithium ion battery in the lithium -ion battery, and achieve the improvement of the battery cycle Performance effect.
Patent Information
- Application Number
- CN202411853438.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The silicon negative electrode material has problems such as volume expansion, instability of SEI film and poor conductivity in lithium-ion batteries, resulting in a degradation of cycling performance.
A negative electrode material including kernel and shell, the kernel is composed of silicon matrix and filling agent. The filling agent includes transition metal carbides and carbon matrix. The shell is located on the surface of the kernel. Between 5%.
The transition metal carbide in the core relieves the stress caused by the expansion of the silicon matrix, improves structural stability, and reduces the contact between the electrolyte and the silicon matrix through the outer shell, reducing side reactions, thereby improving the particle strength of the negative electrode material and the cycle performance of the battery.
Smart Images

Figure CN119340378A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage, and in particular to a negative electrode material and a secondary battery. Background Art
[0002] Silicon anode materials have high theoretical specific capacity and low lithium desorption potential, and are considered as one of the potential candidates for the next generation of high-capacity lithium-ion battery anode materials. However, in practical applications, silicon anode materials have problems such as volume expansion, unstable SEI film, and poor conductivity. In particular, during the process of battery charging and discharging and lithium insertion and extraction, a large volume expansion will occur, which makes the silicon anode material particles easy to break and pulverize, seriously affecting the battery's cycle performance. Summary of the invention
[0003] In view of this, the present application provides a negative electrode material to solve at least one of the above technical problems.
[0004] To achieve the above-mentioned purpose, the present application provides a negative electrode material, which includes a core and a shell. The core includes a silicon matrix and a filler, at least part of the filler is distributed in the silicon matrix, the filler includes a transition metal carbide and a carbon matrix, and the shell is arranged on at least part of the surface of the core. Based on the negative electrode material, the mass proportion of the transition metal element is 0.5% to 5%.
[0005] In some possible implementations, based on the negative electrode material, the mass proportion of the transition metal element is 0.8% to 3.7%.
[0006] In some possible implementations, the filler is also distributed on at least a portion of the surface of the inner core to form an intermediate shell layer.
[0007] In some possible implementations, the thickness of the intermediate shell layer is 50 nm to 100 nm.
[0008] In some possible implementations, the particle strength of the negative electrode material is defined as Cs, Among them, F is the pressure on the particles of the negative electrode material when they break, D is the particle size of the negative electrode material, is pi; Cs is 170 MPa to 350 MPa.
[0009] In some possible implementations, the transition metal carbide includes one or more of molybdenum carbide, titanium carbide, tungsten carbide, tantalum carbide, vanadium carbide, zirconium carbide, chromium carbide, niobium carbide, and hafnium carbide.
[0010] In some possible implementations, the morphology of the transition metal carbide includes one or more of nanoparticles, nanowires, nanotubes, and nanosheets.
[0011] In some possible implementations, the carbon matrix includes one or more of crystalline carbon, amorphous carbon, and transitional carbon.
[0012] In some possible implementations, the material of the shell includes at least one of a carbon material, titanium nitride, boron nitride, silicon nitride, silicon oxide, magnesium oxide, aluminum oxide, silicon carbide, and polyaniline.
[0013] In some possible implementations, the shell has a thickness of 50 nm to 500 nm.
[0014] In some possible implementations, the average particle size of the negative electrode material is 1 μm to 15 μm.
[0015] In some possible implementations, the specific surface area of the negative electrode material is less than or equal to 8 m 2 / g.
[0016] In some possible implementations, the porosity of the negative electrode material is less than or equal to 2.5%.
[0017] In some possible implementations, based on the negative electrode material, the mass proportion of silicon element is 50% to 80%.
[0018] In some possible implementations, the mass proportion of carbon element is 15% to 35% based on the negative electrode material.
[0019] The present application also provides a secondary battery, comprising the above-mentioned negative electrode material.
[0020] In the present application, the transition metal carbide in the inner core has a relatively high structural strength itself, and can be doped on the carbon matrix to form a transition metal carbide-doped carbon matrix, which is dispersed or embedded in the silicon matrix, and can relieve the stress generated by the expansion of the silicon matrix and improve the structural stability of the inner core; the present application also provides an outer shell, which is beneficial to reduce the contact between the electrolyte and the silicon matrix and reduce side reactions, and it also has a certain benefit on the particle strength of the negative electrode material, thereby further improving the cycle performance of the battery.
[0021] Moreover, the particle strength of the negative electrode material and the mass proportion of the transition metal elements in the negative electrode material present a relationship similar to a quadratic function, that is, as the mass proportion of the transition metal elements in the negative electrode material increases, the particle strength of the negative electrode material presents a trend of first increasing and then decreasing. Only by controlling the mass proportion of the transition metal elements within the above range can the particle strength of the negative electrode material be effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic diagram of the structure of a secondary battery provided in one embodiment of the present application during charging.
[0023] Figure 2A schematic diagram of the structure of a secondary battery provided in one embodiment of the present application during discharge.
[0024] Figure 3 This is a SEM cross-sectional image of the negative electrode material provided in Example 2 of the present application.
[0025] Figure 4 This is an EDS surface scan image of the negative electrode material provided in Example 2 of the present application.
[0026] Figure 5 This is the XRD image of the negative electrode material provided in Example 2 of the present application.
[0027] Description of main component reference numerals: Electrode assembly, 100; positive electrode sheet, 101; negative electrode sheet, 102; isolation membrane, 103. DETAILED DESCRIPTION
[0028] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0029] An embodiment of the present application provides a secondary battery, comprising a housing, an electrode assembly and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.
[0030] The outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), for example, a soft-pack battery. In other embodiments, it may also be a steel shell battery, an aluminum shell battery, etc.
[0031] See also Figure 1 and Figure 2 The electrode assembly 100 includes a positive electrode sheet 101, a negative electrode sheet 102 and a separator 103. The separator 103 is disposed between the positive electrode sheet 101 and the negative electrode sheet 102. When an electrolyte (not shown) is provided, when charging, refer to Figure 1 , active ions (such as lithium ions) are deintercalated from the lattice of the positive electrode material (such as the lithiated intercalation compound) of the positive electrode sheet 101, pass through the separator 103 through the electrolyte, reach the negative electrode sheet 102 and insert into the lattice of the negative electrode material. Figure 2, active ions (such as lithium ions) are deintercalated from the lattice of the negative electrode material of the negative electrode sheet 102, pass through the isolation membrane 103 through the electrolyte, reach the positive electrode sheet 101 and are embedded in the lattice of the positive electrode material (such as the lithiated intercalation compound), generating electrons that travel from the negative electrode sheet 102 through the external circuit to the positive electrode sheet 101, and the reverse movement of the electrons forms an electric current that can be used by electrical appliances.
[0032] In some embodiments, the electrode assembly 100 may be a laminated structure, which is formed by alternately stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102. In other embodiments, the electrode assembly 100 may also be a wound structure, which is formed by stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102 in sequence and then winding them.
[0033] Positive electrode The positive electrode sheet 101 includes a positive electrode current collector and a positive electrode material active layer provided on at least one surface of the positive electrode current collector. The positive electrode current collector may be made of aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and a polymer substrate. The positive electrode material active layer includes a positive electrode active material, and the positive electrode active material includes a compound that can reversibly embed and deintercalate lithium ions (i.e., a lithiated intercalation compound). In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) or at least one of lithium iron phosphate (LiFePO4).
[0034] The positive electrode material active layer also includes a binder to bond the positive electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the bonding force between the positive electrode material active layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon.
[0035] The positive electrode material active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0036] Negative plate The negative electrode sheet 102 includes a negative electrode current collector and a negative electrode material active layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may be at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0037] The negative electrode material active layer includes a negative electrode material, the negative electrode material includes a core and a shell, the core includes a silicon matrix and a filler, at least part of the filler is distributed in the silicon matrix, the filler includes a transition metal carbide and a carbon matrix, the shell is provided on at least part of the surface of the core, and based on the negative electrode material, the mass proportion of the transition metal element is 0.5% to 5%. For example, the mass proportion of the transition metal element can be 0.5%, 0.6%, 0.75%, 0.8%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 3.7%, 4%, 4.2%, 4.3%, 5%, or any value within the range formed by any two of the above values.
[0038] In the present application, the transition metal carbide in the inner core has a relatively high structural strength itself, and can be doped on the carbon matrix to form a transition metal carbide-doped carbon matrix, which is dispersed or embedded in the silicon matrix, and can relieve the stress generated by the expansion of the silicon matrix and improve the structural stability of the inner core; the present application also provides an outer shell, which is beneficial to reduce the contact between the electrolyte and the silicon matrix, reduce the side reaction between the negative electrode material and the electrolyte, and has a certain increase in the particle strength of the negative electrode material, thereby further improving the cycle performance of the battery including the negative electrode material of the present application.
[0039] The present application also found that the content of transition metal carbides affects its contribution to the particle strength of the negative electrode material. By regulating the mass proportion of the transition metal elements in the negative electrode material, it is helpful to regulate the particle strength of the negative electrode material. After a lot of research, the inventors found that the particle strength of the negative electrode material and the mass proportion of the transition metal elements in the negative electrode material show a relationship similar to a quadratic function, that is, as the mass proportion of the transition metal elements in the negative electrode material increases, the particle strength of the negative electrode material shows a trend of first increasing and then decreasing. Only by controlling the mass proportion of the transition metal elements within the above range can the particle strength of the negative electrode material be effectively improved.
[0040] It is understandable that when the mass proportion of transition metal elements in the negative electrode material is too low, the volume of the silicon matrix expands significantly during the process of lithium extraction, which can easily lead to the crushing or pulverization of the particles of the negative electrode material including the silicon matrix, destroying the structure of the negative electrode sheet, and causing an increase in the internal stress of the battery, which may cause the negative electrode sheet to break. When the mass proportion of transition metal elements in the negative electrode material is too high, the excess transition metal carbides will destroy the silicon matrix structure during the subsequent heat treatment process, causing the cracking of the negative electrode material including the silicon matrix, reducing the strength of the negative electrode material particles, and exacerbating the volume expansion effect.
[0041] In some embodiments, based on the negative electrode material, the mass proportion of the transition metal element is 0.8% to 3.7%. For example, the mass proportion of the transition metal element can be 0.8%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 3.7%, or any value within the range formed by any two of the above values. When the mass proportion of the transition metal element meets the above range, the particle strength of the negative electrode material can be further improved, and the cyclic expansion effect of the obtained pole piece can be more effectively reduced, and the cyclic stability of the obtained secondary battery can be further improved.
[0042] In some embodiments, the filler is also distributed on at least a portion of the surface of the inner core to form an intermediate shell layer.
[0043] When the transition metal carbides and carbon matrix in the filler are distributed on the surface of the inner core, the transition metal carbides can be doped on the carbon matrix to form a transition metal carbide-doped carbon matrix, which can protect and support the inner core to maintain a more stable structure, which is beneficial to further improve the particle strength of the negative electrode material, so that the negative electrode material can better resist the stress caused by volume change during the charging and discharging process, thereby reducing the risk of negative electrode material particles breaking or pulverizing, reducing the volume expansion effect, and improving the cycle performance of the resulting secondary battery.
[0044] In some embodiments, the thickness of the intermediate shell layer is 50 nm to 100 nm. For example, the thickness of the intermediate shell layer can be 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm. Controlling the thickness of the intermediate shell layer within the above range is conducive to further improving the supporting effect of the intermediate shell layer on the negative electrode material.
[0045] In some embodiments, the particle strength of the negative electrode material is defined as Cs, Among them, F is the pressure on the particles of the negative electrode material when they break, D is the particle size of the negative electrode material, is pi; Cs is 170 Mpa to 350 Mpa. For example, the particle strength Cs can be 170 Mpa, 180 Mpa, 190 Mpa, 200 Mpa, 220 Mpa, 250 Mpa, 300 Mpa, 330 Mpa, 350 Mpa or any value within the range formed by any two of the above values. The negative electrode material with higher particle strength can better resist the stress caused by volume change during the charge and discharge process, thereby reducing the crushing and pulverization of the particles and reducing the cycle expansion rate of the battery including the negative electrode material of the present application.
[0046] In some embodiments, the transition metal carbide includes one or more of molybdenum carbide, titanium carbide, tungsten carbide, tantalum carbide, vanadium carbide, zirconium carbide, chromium carbide, niobium carbide and hafnium carbide. When the negative electrode material includes the above transition metal carbides, it is beneficial to improve the particle strength of the negative electrode material, thereby helping to reduce the volume expansion effect of the negative electrode material.
[0047] In some embodiments, the morphology of the transition metal carbide includes one or more of nanoparticles, nanowires, nanotubes, and nanosheets. The present application has no particular limitation on the morphology of the transition metal carbide. When it is any of the above morphologies or a combination of multiple morphologies, the transition metal carbide can play the role of improving the strength of the negative electrode material particles.
[0048] In some embodiments, the carbon matrix includes one or more of crystalline carbon, amorphous carbon, and transitional carbon.
[0049] In some embodiments, the material of the shell includes at least one of a carbon material, titanium nitride, boron nitride, silicon nitride, silicon oxide, magnesium oxide, aluminum oxide, silicon carbide, and polyaniline.
[0050] In some embodiments, the thickness of the shell is 50 nm to 500 nm. For example, the thickness of the shell can be 50 nm, 60 nm, 80 nm, 100 nm, 150 nm, 200 nm, 300 nm, 450 nm, 500 nm, or any value within the range formed by any two of the above values. Controlling the thickness of the shell within the above range is beneficial to better reduce the contact between the silicon material and the electrolyte and reduce side reactions.
[0051] In some embodiments, the average particle size of the negative electrode material is 1 μm to 15 μm. For example, the average particle size of the negative electrode material can be 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 14 μm, 15 μm, or any value within the range formed by any two of the above values. Controlling the average particle size of the negative electrode material within the above range is conducive to reducing the distance of migration of active ions (such as lithium ions) in the secondary battery, reducing the risk of deterioration of capacity or rate performance in the secondary battery, and at the same time, the appropriate particle size is conducive to maintaining good particle strength of the negative electrode material.
[0052] In some embodiments, the specific surface area of the negative electrode material is less than or equal to 8 m 2 / g. For example, the specific surface area of the negative electrode material can be 1 m 2 / g, 2 m 2 / g, 3 m 2 / g, 4 m 2 / g, 5 m 2 / g, 6 m 2 / g, 7 m 2 / g, 8 m 2 / g or any value within the range formed by any two of the above values. Controlling the specific surface area of the negative electrode material within the above range can reduce the formation of SEI on the surface of the negative electrode material, thereby improving the first coulombic efficiency of the battery prepared from the negative electrode material.
[0053] In some embodiments, the porosity of the negative electrode material is less than or equal to 2.5%. For example, the porosity of the negative electrode material can be 0.5%, 1%, 1.5%, 1.8%, 2.0%, 2.2%, 2.4%, 2.5%, or any value within the range formed by any two of the above values. Porosity refers to the percentage of the pore volume in the material to the total volume of the material in its natural state. The control of the porosity of the negative electrode material within the above range indicates that the pores of the silicon matrix are better filled with the carbon matrix doped with transition metal carbides, which is beneficial to improving the particle strength of the negative electrode material, thereby helping to reduce the volume expansion effect.
[0054] In some embodiments, based on the negative electrode material, the mass percentage of silicon element is 50% to 80%. For example, the mass percentage of silicon element can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, or any value within the range formed by any two of the above values. When the mass percentage of silicon element is controlled within the above range, the lithium-ion battery composed of the negative electrode material can store a higher amount of electricity, which is conducive to improving the initial discharge specific capacity.
[0055] In some embodiments, based on the negative electrode material, the mass proportion of carbon element is 15% to 35%. For example, the mass proportion of carbon element can be 15%, 20%, 25%, 30%, 35%, or any value within the range formed by any two of the above values. The mass proportion of carbon element is controlled within the above range, which can establish a sufficient carbon-based substrate, provide sufficient distribution sites for active substances, and is conducive to forming an effective conductive network, improving conductivity and cycle stability.
[0056] In some embodiments, the expansion rate of the negative electrode sheet based on the above negative electrode material is 34% to 60%. For example, the expansion rate of the negative electrode material can be 34%, 35%, 36%, 37%, 38%, 39%, 40%, 45%, 50%, 55%, 60%, or any value within the range formed by any two of the above values. The expansion rate of the negative electrode sheet within the above range indicates that the negative electrode material particles have good resistance to crushing or pulverization, which is conducive to maintaining good cycle stability of the secondary battery.
[0057] The negative electrode material active layer also includes a binder to bind the negative electrode active material particles to facilitate the formation of a film layer, and can also improve the binding force between the negative electrode material active layer and the negative electrode current collector. In some embodiments, the binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic (ester) styrene butadiene rubber, epoxy resin or nylon, etc.
[0058] The negative electrode material active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0059] Isolation film The isolation membrane 103 includes a membrane layer with a porous structure, and its material includes but is not limited to at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, the isolation membrane 103 can be a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite membrane.
[0060] Electrolytes The electrolyte has the function of conducting ions between the positive electrode sheet 101 and the negative electrode sheet 102. The state of the electrolyte can be one or more of a gel state, a solid state and a liquid state. In some embodiments, the electrolyte is an electrolyte. The electrolyte plays the role of conducting active ions between the positive electrode sheet 101 and the negative electrode sheet 102. In some embodiments, the electrolyte includes a lithium salt and an organic solvent. The lithium salt can be selected from but not limited to one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetraphenylborate (LiB(C6H5)4), lithium methanesulfonate (LiCH3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(SO2CF3)2, tris(trifluoromethylsulfonyl)methyl lithium (LiC(SO2CF3)3), lithium bis(oxalatoborate) (LiBOB) and lithium difluorophosphate (LiPO2F2). For example, the lithium salt is selected from LiPF6 because it can give high ionic conductivity and improve cycle characteristics. The organic solvent can be a carbonate compound, a carboxylate compound, an ether compound, Compounds, nitrile compounds, other organic solvents or combinations thereof. Examples of carbonate compounds include, but are not limited to, diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethylmethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.
[0061] Another embodiment of the present application provides a method for preparing a negative electrode material, comprising: The first step is to provide porous silicon.
[0062] In some embodiments, the silicon matrix with a porous structure can be obtained by etching with an acid solution. For example, taking silicon oxide as an example, micron-sized silicon oxide is placed in a box furnace and heat-treated at about 900°C in an inert gas atmosphere to generate particles composed of silicon and silicon oxide by a disproportionation reaction. The obtained particles are etched with a 2 mol / L hydrofluoric acid solution to remove the silicon oxide component, and then washed and vacuum dried to obtain a silicon matrix with a porous structure, i.e., porous silicon.
[0063] Step 2: applying pressure to allow the impregnation solution to enter the interior of the porous silicon, the impregnation solution comprising a transition metal salt solution and a carbon source solution, and then heating and drying the porous silicon treated with the impregnation solution to obtain a composite material.
[0064] In some embodiments, the impregnation liquid is forced into the porous silicon by applying pressure, and a small amount of the impregnation liquid that has not entered the porous silicon remains on the surface of the porous silicon. The impregnation liquid remaining on the surface of the porous silicon can form an intermediate shell layer during the heat treatment reaction to coat the surface of the inner core. It can be understood that when the intermediate shell layer and the outer shell formed subsequently exist at the same time, the intermediate shell layer is closer to the inner core than the outer shell.
[0065] In some embodiments, this step specifically includes placing the porous silicon prepared in step 1 in a pressure impregnation device, evacuating to 50 Pa, then inputting an impregnation solution, the impregnation solution including a transition metal salt solution and a carbon source solution, then applying a pressure of 5 Mpa, heating to 120°C, and keeping warm for 0.5 h to 1 h, so that the pores of the porous silicon are filled with the impregnation solution, and obtaining a composite material after drying.
[0066] In some embodiments, the concentration of the transition metal salt solution is 2 mol / L, and based on the volume of the impregnating solution, the volume proportion of the transition metal salt solution is greater than or equal to 10% and less than or equal to 70%. Controlling the volume proportion of the transition metal salt solution within the above range is beneficial to controlling the mass proportion of the transition metal element in the obtained negative electrode material, thereby facilitating the regulation of the particle strength of the obtained negative electrode material.
[0067] In some embodiments, the transition metal element in the transition metal salt solution includes one or more of molybdenum, titanium, tungsten, tantalum, vanadium, zirconium, chromium, niobium and hafnium. Based on the above transition metal elements, the above transition metal salt solution can illustratively include sodium molybdate solution, ammonium molybdate solution, metatitanic acid solution, titanium tetrachloride solution, tetrabutyl titanate solution, sodium tungstate solution, ammonium metatungstate solution, tungsten chloride solution, tantalum fluoride solution, sodium metavanadate solution, zirconium chloride solution, chromium chloride solution, sodium chromate solution, niobium oxalate solution, hafnium tetrachloride solution, etc.
[0068] In some embodiments, the carbon source in the carbon source solution includes one or more of asphalt, glucose, polyethylene, polyvinyl alcohol, polyethylene glycol, polyaniline, epoxy resin, phenolic resin, and acrylic resin in liquid phase.
[0069] Step 3: Mix the composite material with the carbon source gas and perform heat treatment in a reducing gas atmosphere to obtain the negative electrode material.
[0070] During the heat treatment process, the impregnation liquid inside the porous silicon undergoes an oxidation-reduction reaction in the inner core area to form a transition metal carbide-doped carbon matrix. If a small amount of impregnation liquid remains on the surface of the porous silicon, an intermediate shell layer of the transition metal carbide-doped carbon matrix is formed. The carbon source gas will decompose and deposit on the surface of the material to form an outer shell, which is mainly pure carbon.
[0071] In some embodiments, the carbon source gas includes one or more of propane, propylene, methane, and acetylene.
[0072] In some embodiments, the reducing gas in the reducing gas atmosphere includes one or more of hydrogen, carbon monoxide, and ammonia.
[0073] In some embodiments, the flow rate of the carbon source gas or the reducing gas is 0.5 L / min to 2 L / min. Controlling the flow rate of the carbon source gas or the reducing gas within the above range is conducive to more complete contact and reaction with the composite material.
[0074] In some embodiments, the heat treatment temperature is 600°C to 800°C, the heat treatment time is 1 h to 4 h, and the heating rate during the heat treatment is 3°C / min to 5°C / min. The heat treatment temperature and time are controlled within the above range, which is beneficial to promoting the conversion of the impregnation liquid inside and on the surface of the porous silicon, and is also beneficial to the full cracking of the carbon source gas, and is beneficial to the formation of the preset core and shell.
[0075] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.
[0076] Embodiment 1: A negative electrode material, the preparation method comprising: S1, 100 g of silicon oxide with an average particle size of 3 μm was placed in a box furnace, nitrogen was introduced, the temperature was increased to 900 °C at a heating rate of 3 °C / min, kept at this temperature for 4 h, cooled to room temperature, mixed with 500 mL of 2 mol / L hydrofluoric acid solution, etched for 40 min, and then washed and vacuum dried to obtain porous silicon.
[0077] S2, place the porous silicon obtained in S1 in a pressure impregnation equipment, evacuate to 50 Pa, input 60 mL of impregnation solution, the impregnation solution includes a carbon source and a metal ion salt solution, the carbon source is liquid asphalt, the metal ion salt solution is sodium molybdate solution, and the sodium molybdate solution accounts for 20% of the volume of the impregnation solution, then apply a pressure of 5 MPa, raise the temperature to 120 °C, and keep it warm for 1 h, and then dry it to obtain a composite material.
[0078] S3, placing the obtained composite material in a rotary kiln, introducing a carbon source gas and a reducing gas for heat treatment; wherein the carbon source gas is propylene, the flow rate of propylene is 1.0 L / min, the reducing gas is hydrogen, the flow rate of hydrogen is 0.5 L / min, the heat treatment temperature is 700 ℃, the heating rate is 5 ℃ / min, the holding time after reaching the heat treatment temperature is 2 h, and then the temperature is lowered to room temperature to obtain the negative electrode material.
[0079] Embodiment 2: The difference from Example 1 is that in S2, the metal ion salt solution is a metatitanic acid solution.
[0080] Embodiment 3: The difference from Example 1 is that in S2, the metal ion salt solution is a sodium tungstate solution.
[0081] Embodiment 4: The difference from Example 1 is that in S2, the metal ion salt solution is a tantalum fluoride solution.
[0082] Embodiment 5: The difference from Example 1 is that in S2, the metal ion salt solution is a sodium metavanadate solution.
[0083] Embodiment 6: The difference from Example 1 is that in S2, the metal ion salt solution is a zirconium chloride solution.
[0084] Embodiment 7: The difference from Example 1 is that in S2, the metal ion salt solution is a chromium chloride solution.
[0085] Embodiment 8: The difference from Example 1 is that in S2, the metal ion salt solution is a sodium chromate solution.
[0086] Embodiment 9: The difference from Example 1 is that in S2, the metal ion salt solution is a niobium oxalate solution.
[0087] Embodiment 10: The difference from Example 1 is that in S2, the metal ion salt solution is a hafnium tetrachloride solution.
[0088] Embodiment 11: The difference from Example 1 is that in S3, the holding time of the heat treatment is 1 h.
[0089] Embodiment 12: The difference from Example 1 is that in S3, the holding time of the heat treatment is 3 h.
[0090] Embodiment 13: The difference from Example 1 is that in S3, the heat treatment temperature is 600°C.
[0091] Embodiment 14: The difference from Example 1 is that in S3, the temperature of the heat treatment is 800°C.
[0092] Embodiment 15: The difference from Example 1 is that in S2, the sodium molybdate solution accounts for 10% of the volume of the impregnation solution.
[0093] Embodiment 16: The difference from Example 1 is that in S2, the sodium molybdate solution accounts for 30% of the volume of the impregnation solution.
[0094] Embodiment 17: The difference from Example 1 is that in S2, the sodium molybdate solution accounts for 40% of the volume of the impregnation solution.
[0095] Embodiment 18: The difference from Example 1 is that in S2, the sodium molybdate solution accounts for 50% of the volume of the impregnation solution.
[0096] Embodiment 19: The difference from Example 1 is that in S2, the sodium molybdate solution accounts for 60% of the volume of the impregnation solution.
[0097] Embodiment 20: The difference from Example 1 is that in S2, the sodium molybdate solution accounts for 70% of the volume of the impregnation solution.
[0098] Comparative Example 1: The difference from Example 1 is that in S2, the impregnation solution does not contain sodium molybdate solution.
[0099] Comparative Example 2: The difference from Example 1 is that in S2, the sodium molybdate solution accounts for 5% of the volume of the impregnation solution.
[0100] Comparative Example 3: The difference from Example 1 is that in S2, the sodium molybdate solution accounts for 90% of the volume of the impregnation solution.
[0101] Please refer to Table 1 for some of the preparation conditions of Examples 1-20 and Comparative Examples 1-3 of the present application.
[0102] Table 1. Partial preparation conditions of Examples 1-20 and Comparative Examples 1-3 of the present application The physical properties and electrochemical properties of the negative electrode materials obtained in the above examples 1-20 and comparative examples 1-3 were tested, and the testing methods were as follows: Negative electrode material particle strength test: Under the action of electromagnetic force, the corresponding force on the pressure head gradually increases at a certain speed. When the particle's rupture point is reached, the particle ruptures. At this time, the resistance to the pressure head disappears, causing its displacement to drop rapidly. The instrument determines its rupture point (displacement increases rapidly) by recording the displacement of the pressure head in real time, and records the pressure on the particle at this time as pressure F. The relationship between pressure F, particle size D and particle strength Cs is: Test of the mass proportion of transition metal elements in negative electrode materials: The mass proportion of transition metal elements in negative electrode materials is measured by ICP and other methods.
[0103] Test of transition metal carbides in negative electrode materials: X-ray diffraction (XRD) is used to analyze the negative electrode materials. In the XRD image, the metal elements in the negative electrode materials are mainly displayed as transition metal carbide peaks, indicating that the metal elements in the negative electrode materials mainly exist in the form of transition metal carbides.
[0104] The thickness test of the shell of the negative electrode material: Use a scanning electron microscope (SEM) to analyze the cross-section of the negative electrode material and measure the thickness of the corresponding shell.
[0105] Average particle size test of negative electrode materials: Observe material particles through field emission scanning electron microscopy or transmission electron microscopy, randomly measure the particle sizes of 5 to 10 material particles through a scale, and take the average value of the particle size as the final average particle size of the material particles.
[0106] Specific surface area test of negative electrode materials: The specific surface area of the powder sample was tested by gas adsorption method (nitrogen adsorption multi-point BET) at low temperature controlled by liquid nitrogen cooling using the American Micromeritics TriStar3000&3020 specific surface area and pore size analyzer.
[0107] Porosity test of negative electrode material: P = Vo / (Vo+V) × 100%, where P is the porosity of the material (%) and Vo is the pore volume of the material (cm 3 ), V is the absolute dense volume (cm 3). Vo is obtained by testing with the American Micromeritics TriStar3000&3020 specific surface area and pore size analyzer, and V is obtained by testing and conversion with the true density tester AccuPyc 1340.
[0108] Test of the mass percentage of carbon element in negative electrode material: The carbon element of the negative electrode material is analyzed and determined by an infrared carbon-sulfur analyzer, and the mass percentage of the carbon element obtained is the mass percentage of the carbon element in the negative electrode material.
[0109] Test of the mass percentage of silicon material in the negative electrode material: The negative electrode material is first placed in an oxygen atmosphere and burned in Nanyang Xinyu's SA2-9-17TP box-type atmosphere furnace to react the silicon in the sample into silicon dioxide. The carbon is burned and discharged as carbon dioxide. The burned residue is then placed in a nitric acid solution to fully react and remove the metal. The residue is washed, dried, and weighed to calculate the mass percentage of silicon.
[0110] Electrochemical performance test: The negative electrode material, conductive agent and binder are mixed in a solvent in a mass percentage of 90:5:5, the conductive agent is Super P, and the binder is PAA. The mixed slurry is coated on the copper foil current collector, dried and pressed to obtain the electrode. Then, CR2025 button batteries are assembled, and the electrochemical performance is tested using a blue power test system. The electrolyte is 1 mol / L LiPF6 / EC / DMC (1:1). The capacity and first coulombic efficiency of the negative electrode material are tested at a current density of 0.1 C, and the 50-week cycle retention rate is tested at a current density of 1 C. After repeating 50 cycles, the thickness of the battery electrode is measured with a micrometer to obtain the volume expansion rate.
[0111] Please refer to Table 2 for some of the above test results.
[0112] Taking Example 2 as an example, a cross section of the negative electrode material was analyzed using a scanning electron microscope (SEM), an energy dispersive X-ray spectrometer (EDS) and an X-ray diffraction (XRD).
[0113] See also Figure 3 In the SEM image, an intermediate shell and an outer shell with obvious interface distinction were observed in the outer layer of the inner core of the negative electrode material.
[0114] See also Figure 4 , a surface scan is performed on the cross-section of the negative electrode material sample to obtain the element distribution information of the entire area. In the EDS scanning image, it can be observed that the negative electrode material includes Si, Ti and C elements.
[0115] See also Figure 5 ,In the XRD image, the metal elements in the negative electrode material are mainly shown as peaks of transition metal carbides (TiC), indicating that the transition metal elements in the negative electrode material exist mainly in the form of transition metal carbides.
[0116] Table 2. Performance test results of Examples 1-20 and Comparative Examples 1-3 of the present application Embodiments 1-20 use different transition metal salt solutions (such as embodiment 1-10) or different process conditions (such as embodiments 1, 11-20) to prepare negative electrode materials, so that the obtained negative electrode materials have transition metal elements in a preset range of mass proportions, and form an appropriate distribution of a carbon matrix doped with transition metal carbides in the negative electrode materials, which provides higher particle strength for the negative electrode materials, enables the obtained negative electrode sheets to maintain lower expansion after charge and discharge cycles, and enables the obtained secondary batteries to have higher capacity, first coulomb efficiency and cycle stability.
[0117] Compared with Example 1, no transition metal salt solution was added during the preparation process of Comparative Example 1, and the obtained negative electrode material contained almost no transition metal elements, resulting in significantly lower particle strength of the negative electrode material and obvious expansion effect of the pole piece, which affected the cycle stability of the secondary battery.
[0118] Compared with Example 1, in the preparation process of Comparative Example 2, a metal ion salt solution with a smaller volume percentage is added to form an impregnation solution, and the content of transition metal elements in the prepared negative electrode material is low, that is, the content of transition metal carbides in the negative electrode material may be low. The mass percentage of transition metal elements in the negative electrode material is lower than the preset lower limit, resulting in a more obvious volume expansion of the silicon matrix during the process of lithium insertion and extraction of the negative electrode material, which easily leads to the crushing or pulverization of particles of the negative electrode material including the silicon matrix, destroying the structure of the negative electrode sheet, and also causing an increase in the internal stress of the battery, which is not conducive to the use of capacity, and the first coulomb efficiency of the secondary battery obtained is reduced and the cycle stability is poor.
[0119] Compared with Example 1, a larger volume percentage of metal ion salt solution is added during the preparation of Comparative Example 3, and the mass percentage of the transition metal element in the negative electrode material in the formed impregnation solution is higher than the preset upper limit value, that is, the content of transition metal carbide in the negative electrode material may be high. Excessive transition metal carbides will destroy the silicon matrix structure during the subsequent heat treatment process, causing cracking of the particles of the negative electrode material including the silicon matrix, reducing the strength of the negative electrode material particles, aggravating the volume expansion effect of the obtained secondary battery, and being not conducive to the performance of the capacity. The first coulomb efficiency of the obtained secondary battery is reduced and the cycle stability is poor.
[0120] In summary, the present application uses an improved preparation method to obtain a negative electrode material with higher particle strength, and the volume expansion effect is significantly improved, which is beneficial to the capacity of the obtained secondary battery, so that the obtained secondary battery has a higher first coulomb efficiency and good cycle stability. The present application also controls the preparation process conditions to control the mass proportion of transition metal elements in the obtained negative electrode material, thereby further improving the electrochemical performance of the obtained secondary battery.
[0121] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A negative electrode material, characterized in that: The negative electrode material includes a core and a shell, the core includes a silicon matrix and a filler, at least part of the filler is distributed in the silicon matrix, the filler includes a transition metal carbide and a carbon matrix, the shell is arranged on at least part of the surface of the core, and based on the negative electrode material, the mass proportion of the transition metal element is 0.5% to 5%.
2. The negative electrode material according to claim 1, characterized in that Based on the negative electrode material, the mass proportion of the transition metal element is 0.8% to 3.7%.
3. The negative electrode material according to claim 1, characterized in that The filler is also distributed on at least a portion of the surface of the core to form an intermediate shell layer.
4. The negative electrode material according to claim 3, characterized in that The thickness of the intermediate shell layer is 50 nm to 100 nm.
5. The negative electrode material according to claim 1, characterized in that The particle strength of the negative electrode material is defined as Cs, Wherein, F is the pressure on the particles of the negative electrode material when they are broken, D is the particle size of the particles of the negative electrode material, is pi; Cs is 170 MPa to 350 MPa.
6. The negative electrode material according to claim 1, characterized in that The transition metal carbide satisfies at least one of the following conditions: (1) The transition metal carbide includes one or more of molybdenum carbide, titanium carbide, tungsten carbide, tantalum carbide, vanadium carbide, zirconium carbide, chromium carbide, niobium carbide and hafnium carbide; (2) The morphology of the transition metal carbide includes one or more of nanoparticles, nanowires, nanotubes and nanosheets.
7. The negative electrode material according to claim 1, characterized in that The carbon matrix includes one or more of crystalline carbon, amorphous carbon, and transition carbon.
8. The negative electrode material according to claim 1, characterized in that The housing satisfies at least one of the following conditions: (1) The material of the shell includes at least one of carbon material, titanium nitride, boron nitride, silicon nitride, silicon oxide, magnesium oxide, aluminum oxide, silicon carbide and polyaniline; (2) The thickness of the shell is 50 nm to 500 nm.
9. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies at least one of the following conditions: (1) The average particle size of the negative electrode material is 1 μm to 15 μm; (2) The specific surface area of the negative electrode material is less than or equal to 8 m 2 / g; (3) The porosity of the negative electrode material is less than or equal to 2.5%; (4) Based on the negative electrode material, the mass proportion of silicon element is 50% to 80%; (5) Based on the negative electrode material, the mass proportion of carbon element is 15% to 35%.
10. A secondary battery, characterized in that: Comprising the negative electrode material as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Coated negative electrode material and preparation method thereof
CN106558683A
Inert coating-coated silicon oxide composite material for lithium ion secondary battery and preparation thereof
CN113948692A
Negative electrode active material for secondary battery and secondary battery using same
CN115398674A
Negative electrode and lithium ion battery using same
CN116914084A
Negative electrode material and battery
CN119092690A
Cited By
Pole piece slurry of high-rate lithium battery and coating process of pole piece slurry
CN120613347A